Notorious in the neighborhood : sex and families across the color line in Virginia, 1787-1861 - Rothman, Joshua D. (UNC Press law publications., 2003)
This text examines interracial sexual relationships under slavery. While laws militated against interracial sex in Virginia before the Civil War it was ubiquitous throughout the state. The customery toleration of sex across the colour line both supported and undermined racism.